Peran Pendidikan Islam Dalam Mendorong Perubahan Sosial Di SMA Plus Budi Luhur Mandiri - Jarya, Haenul; Yasin, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2025)
This study examines the role of Islamic education in driving social change at SMA Plus Budi Luhur Mandiri. The research aims to identify the contributions of Islamic education to character development, social awareness, and student participation in social change within the school and community. A qualitative approach with a phenomenological design was employed. Data were collected through interviews, observations, and documentation, then analyzed using Miles and Huberman's interactive model. The findings reveal that Islamic education shapes students' discipline, responsibility, and politeness; enhances social awareness through empathy teaching; and fosters student involvement in social activities such as community service. Islamic education is proven to be not only a means of knowledge transfer but also an effective tool for creating positive social change.